Silenced Voices: Hungarian Plays from Transylvania. Selected and translated by Csilla Bertha and Donald E. Morse. Dublin: Carysfort Press, 2008. 283 pages. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2012)
This finely produced volume contains five plays by Hungarian authors living in Transylvania (part of Romania since 1920) in the last decades of the twentieth century, whom we are justified to call, according to the translators’ introduction, “the forgotten playwrights of Central Europe” (1). “Falling through the Cracks” as the subtitle of the introduction encapsulates the idea that since the Trianon Peace Treaty following World War I with the significant border changes of the region, Hungarian writers living in Romania and continuing to use the Hungarian language in their literary works, have scarcely reached a wider audience chiefly because of their minority status. Therefore it is really a cause for celebration that a volume of plays by eminent Transylvanian playwrights is now added to the few previously published English translations of the considerable bulk of quality Hungarian literature coming from Romania. The careful selection and successful translation of the material praises the unique collaboration of Csilla Bertha and Donald E. Morse, a married couple whose names are well-known in international scholarship, in the field of Irish, American and Comparative Studies. She is Hungarian and he is American, forming a combination which, in this case, has resulted in fruitfully joining an intimate understanding of the historical, socio-cultural and Biblical embeddedness of the Hungarian texts with reliable knowledge of what will sound acceptable, meaningful as well as accurately nuanced to an English-speaking audience. Their ambitiously written introduction sets the tone of trying to make more friends for this neglected segment of world literature as well as offering indispensable information to assist readers (theatre practitioners among them, hopefully) in enjoying the artistic values of the plays following as fully as possible.